Respuesta :

6/h -1 =-3
6/h = -2
6=-2h
h= -3

Answer:

ℎ = −3

Step-by-step explanation:

6

1

=

3

\frac{6}{h}-1=-3

h6​−1=−3

6

+

(

1

)

=

3

\frac{6}{h}+\frac{h\left(-1\right)}{h}=-3

h6​+hh(−1)​=−3

2

Combine fractions with common denominator

6

+

(

1

)

=

3

\frac{6}{h}+\frac{h\left(-1\right)}{h}=-3

h6​+hh(−1)​=−3

6

+

(

1

)

=

3

\frac{6+h\left(-1\right)}{h}=-3

h6+h(−1)​=−3

3

Re-order terms so constants are on the left

6

+

(

1

)

=

3

\frac{6+h\left(-1\right)}{h}=-3

h6+h(−1)​=−3

6

=

−3